Mass observers making meaning: religion, spirituality and atheism in late 20th-century Britain - Hinton, James (The mass-observation critical series, 2023)
Introduction: Puzzled People? -- Belief and Disbelief -- Death and Afterwards -- Religion and Science -- Uses of the Paranormal -- Moments in our Time -- A Pagan Priestess.